(untitled) (Journal of Asian Development Studies, 2025)
The foundation of human connection is effective communication, which affects everything from interpersonal relationships to organisational success. It is a process in which the sender’s intent is mirrored in the message that the recipient appropriately receives. Human existence depends on communication, and the quality of that communication has a direct effect on educational culture. The core aim of the research is to explore the impact of incomplete messages on institutional effectiveness and individuals’ morale, and also to identify the elements that enhance effective communication. The qualitative phenomenological research design is used.Semi-structured interviews were conducted with 10 individuals to collect in depth data. The sample was selected by using a purposive sampling technique. The collected data was analysed by using thematic analysis. Two major themes emerged: the impact of ineffective communication on both the institutional environment and individuals. The second theme unfolds the elements of effective communication. The results highlighted that incomplete messages tend to delay organisational tasks, reduce the efficiency of work and defame the organisation. In contrast, incomplete messages also have a negative impact on individuals who suffer from anxiety, stress and conflicts. The findings also highlighted three significant elements of effective communication, which include the addition of specific vocabulary in the sentences to bring concreteness and the use of the 5Ws in messages to make them complete to avoid misunderstanding. The recommendations are proposed based on derived themes to address the issues.